Strategies for working with families of people addicted to alcohol. Prospects for professionals - Dobińska, Gabriela; Cieślikowska‑Ryczko, Angelika (Rodzina w systemie wsparcia i pomocy osobom z problemem alkoholowym, 2020)
Research into the experience of alcohol crisis within the family has allowed to gather dozens of in-depth interviews, not only with parents of adult children addicted to alcohol, but also with people involved in their support, both informally and professionally. The professional experience of the latter (professionals – social workers, therapists, doctors) has become the main subject of our deliberations. A brief description of the needs of families and the institutional response to these needs led us to the second part of the article, in which we look at various research trails, as well as theoretical and methodological inspirations. We are considering the concept of professional activities and their standardization, and we add to our considerations the concept of intermediate work, by characterizing its types. In the interactive framework, we deliberate (avoiding generalizations and conclusions) on relationships oriented towards supporting and helping parents in an alcohol crisis. In the last key part we try to answer the following questions: What strategies do the respondents apply? How do they characterize their actions and how do they define a parent as an interaction partner? The article is a result of a project titled “Family in the system of social support and help for people with alcohol problems. Biographical research with the participation of parents of adult children addicted to alcohol” carried out as the following task: “Supporting scientific research in the area of problems resulting from the use of alcohol”. The project conducted by the research team from the Special Pedagogy Laboratory at the Faculty of Education Sciences is financed by the Gambling Problem Solving Fund, as part of the National Health Program for the years 2016–2020.